Molecular characterization of canine BCR-ABL–positive chronic myelomonocytic leukemia before and after chemotherapy - Culver, Sarah (Vet Clin Pathol, 2013)
Genetic aberrations linked to tumorigenesis have been identified in both canine and human hematopoietic malignancies. While the response of human patients to cancer treatments is often evaluated using cytogenetic techniques, this approach has not been used for dogs with comparable neoplasias. The aim of this study was to demonstrate the applicability of cytogenetic techniques to evaluate the cytogenetic response of canine leukemia to chemotherapy. Cytology and flow cytometric techniques were used to diagnose chronic myelomonocytic leukemia in a dog. High-resolution oligonucleotide array comparative genomic hybridization (oaCGH) and multicolor fluorescence in situ hybridization (FISH) were performed to identify and characterize DNA copy number aberrations (CNAs) and targeted structural chromosome aberrations in peripheral blood WBC at the time of diagnosis and following one week of chemotherapy. At the time of diagnosis, oaCGH indicated the presence of 22 distinct CNAs, of which trisomy of dog chromosome 7 (CFA 7) was the most evident. FISH analysis revealed that this CNA was present in 42% of leukemic cells; in addition, a breakpoint cluster region-Abelson murine leukemia viral oncogene homolog (BCR-ABL) translocation was evident in 17.3% of cells. After one week of treatment, the percentage of cells affected by trisomy of CFA7 and BCR-ABL translocation was reduced to 2% and 3.3%, respectively. Chromosome aberrations in canine leukemic cells may be monitored by molecular cytogenetic techniques to demonstrate cytogenetic remission following treatment. Further understanding of the genetic aberrations involved in canine leukemia may be crucial to improve treatment protocols.